How affordable are accessible locations? Neighborhood affordability in U.S. urban areas with intra-urban rail service. (September 2021) - Singer, Matan E.
Abstract: Housing and transportation affordability is a major problem for low-income households, yet studies on the issue tend to focus on the average household. Consequently, relatively little is known about the factors that affect affordability for low-income households and the neighborhoods that are affordable to them. This study addresses these issues and examines how housing and transportation affordability varies across neighborhoods with different built environments and the affordability of these neighborhoods to households from different income groups. The analysis is based on a unique data set comprised of neighborhoods within the urbanized areas of twenty-seven U.S. metropolitan areas with intra-urban rail service. Neighborhoods are further categorized into six types based on their built environments and distance from a rail station. The results suggest that transit-rich neighborhoods are more affordable than auto-oriented ones, mainly due to lower transportation costs. However, only a small share of neighborhoods and housing units are affordable to very-low income households. The results have implications to the way affordability is measured and understood as well as to efforts to alleviate affordability problems. Highlights: Spatial analysis of location affordability in U.S. urban areas with rail service Categorize neighborhoods based on their built environment and rail proximity Transit-rich neighborhoods are more affordable than auto-oriented neighborhoods. Only 6% of neighborhoods are affordable to very-low income households.